FREQUENCY OF HYPOMAGNESEMIA IN RHEUMATOID ARTHRITIS PATIENTS WITH TRPM6 GENE POLYMORPHISM IN PESHAWAR - Asmat, Sara; Shuaib, Ambar; Hassan, Javaid; Fareed, Shahid; Hussain, Shah; Farooq, Ghulam (Khyber Journal of Medical Sciences, 2022)
Objectives: The goal of the current study was to find the frequency of hypomagnesemia in rheumatoid arthritis (RA) patients and possible association between TRPM6 gene polymorphism and onset of rheumatoid arthritis. Material and Methods: A cross-sectional analysis was performed from June 2019 till May 2020. 150 patients and 150 control samples were included in the study from assigned health care facilities of Peshawar and blood samples and other information was collected. The experimental work was performed in Department of Physiology, Institute of Basic Medical Sciences, Khyber Medical University, Peshawar. Non-probability sampling technique was used, and written informed consent was obtained from the subjects. Serum magnesium levels were measured. A modified salting out protocol was used to extract DNA. The TRPM6 gene polymorphism was genotyped using the ARMS-PCR (amplification refractory mutation system polymerase chain reaction) method. The Chi-square test was used to determine the relationship between TRPM6 genotypes and rheumatoid arthritis disease. The odds ratio at the 95 percent confidence level was used to calculate the risk of rheumatoid arthritis. Results: According to our results, serum magnesium level was found normal in 110 (36.67%) patients with RA. Hypomagnesemia was found in 35 (11.67%) while magnesium levels of 05 (1.67%) patients were found to be at the borderline. A significant association was found between TRPM6 gene polymorphism (rs2274924) and hypomagnesemia in patients with RA (p-value <0.05) but was not a risk factor for RA in predisposed people (odds Ratio = 0.23).